Improved Boundary Conditions for a 3D DEM Simple Shear Model - Yao Li; Peifeng Su; Zhe Wang (Advances in Civil Engineering)
In this study, a 3D simple shear model using DEM is built based on the boundary condition of an NGI-type bidirectional simple shear apparatus. Stack of rings used as lateral constraints in a bidirectional simple shear test is modelled by layers of clumps which is possible to be moved by particles; different contact types and parameters are used to model the sand-loading caps, sand-latex membrane, and sand-sand contacts. A simple shear test using the bidirectional simple shear apparatus is performed for the calibration of the 3D DEM simple shear model. By analyzing the simulation results, the following can be concluded. (1) Rings generated by clumps can provide an accurate boundary condition, effective in computation since no contact force is needed for a clump. (2) In the simulation, the orientation of average contact force changed dramatically during shear. It is in the vertical direction (90°) before shear and changes to 45° at 40% shear strain. No shear band is observed which is consistent with the test, and particles move uniformly. (3) In the simulation, the degree of noncoaxiality is the greatest at the beginning of shear, and it is decreased during shear. However, the degree of noncoaxiality is still large at 20% shear strain where there is a 10° difference between the rotation angle of principal stress and principal strain increment.